2019
DOI: 10.1039/c8nj06259e
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical modeling of pKa's of thiol compounds in aqueous solution

Abstract: The pKa's of different kinds of thiols (R-SH) were investigated by using the M06-2X method with a SMDsSAS model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 112 publications
0
15
0
Order By: Relevance
“…Fluorescence quenching experiments showed that 4-fluorothiophenol strongly quenches the excited state of the CdSe/CdS QDs. The researchers noted the oleylamine ligands decorating the QDs are able to deprotonate the thiol (e.g., for 4-fluorothiophenol, p K a (calc) = 8.0 in H 2 O) 910 to form the thiolate anion and that this thiolate anion likely plays an important role in quenching the hole within the VB. Additional experiments using stoichiometric amounts of TEMPO yielded the TEMPO-thiophenol adduct, suggesting that thiyl radicals are generated over the course of the reaction.…”
Section: Reductive Transformations Of Carbonyls Imines and Other X=y Functional Groups Through Photochemical And Electrochemical Pcet Promentioning
confidence: 99%
“…Fluorescence quenching experiments showed that 4-fluorothiophenol strongly quenches the excited state of the CdSe/CdS QDs. The researchers noted the oleylamine ligands decorating the QDs are able to deprotonate the thiol (e.g., for 4-fluorothiophenol, p K a (calc) = 8.0 in H 2 O) 910 to form the thiolate anion and that this thiolate anion likely plays an important role in quenching the hole within the VB. Additional experiments using stoichiometric amounts of TEMPO yielded the TEMPO-thiophenol adduct, suggesting that thiyl radicals are generated over the course of the reaction.…”
Section: Reductive Transformations Of Carbonyls Imines and Other X=y Functional Groups Through Photochemical And Electrochemical Pcet Promentioning
confidence: 99%
“…While EDL and VDW interactions are likely to stabilize this film, the strong attraction resulting from the hydrophobic interaction will lead to the film breakage and the further bubble attachment to the surface by the formation of a three-phase contact line (TPC, three phases are surface, water, air) [46,47]. In our case, bubbles are negatively charged [48], the gold surfaces produced are neutral at the pH considered (7.4 [49]), thus the electrostatic interactions are not attractive. Regarding the VDW forces, although not known for our system, the Hamaker constant of the interactions air-water-hydrocarbon is negative [50].…”
Section: Figure 3 Probing the Interactions Between Bubbles And Hydrophobic Surfaces A) Schematic Representation Of The Interaction Betweementioning
confidence: 83%
“…The methodology consists of using three explicit molecules of water in addition to a continuum solvent model. After some experiments and benchmarking of levels of theory (see Supporting Information), the model was applied to α‐ d ‐Glc‐2Ac_H and α‐ d ‐Glc‐3Ac_H using m062x/6‐31+G(d,p)/SMD=water as level of theory for the optimization of the structures which has shown excellent results with thiols [33] . After some benchmarking, m062x/cc‐pvtz/SMD=water level of theory was used for energy calculations.…”
Section: Resultsmentioning
confidence: 99%